Fique em casa? Estudo antropológico sobre os desdobramentos da pandemia da COVID-19 nos encontros entre o Consultório na Rua e as pessoas em situação de rua no município de João Pessoa/PB - Carvalho, Bruna Carla Cordeiro de (2022)
ABSTRACT: This research aims to outline the consequences of the COVID pandemic for street clinics attending to homeless people on the streets of João Pessoa, Brazil. The investigation intends to understand the macropolitics implemented during the pandemic and then analyze the micropolitics of the local reality of the homeless population. It is an ethnographic fieldwork carried out while accompanying the care provided by the itinerant clinic and its van, from preventive care until the early stages of vaccination. This ethnography has dedicated itself to the urban intricacies, healthcare attendance and the corporealities of homelessness, all of which highlight the scope of invisibility experienced by this population. Several inconsistencies are perceived between the public policies regarding the virus and the homeless population, such as “stay at home” and “wash your hands”. The fundamental premise of this research is the antagonism which permeates the fight against the pandemic and the structural suffering constantly endured by those living on the streets, who are also marked by infirmities already present and reunited within their vulnerable bodies in a real syndemic.